Schooling for Sustainable Development
XVIII, 222 p.
Keywords: "This book Schooling for Sustainable Development: A Focus on Australia, New Zealand and the Oceanic Region, is the product of passionate interests of teachers, scholars and researchers located in diverse parts of the Australasian region. Working with their colleagues within local contexts they have conducted research and gathered together information for practitioners and students interested in learning more about sustainable lifestyle practices. Some of the work has taken place in remote locations and some has been in within the confines of major cities. The Australasian Region brings together people and cultures that link traditional economies to global networks and lifestyles. Diverse terrain, politics and responses typify the region. Close to Asia there are lingering ties with old European ways and cultural beliefs. The major economies of Australia and New Zealand provide the lead with development practices for lesser economies such as Papua New Guinea, Fiji and the many island nations scattered throughout the South Pacific. This complexity is not easily represented. Key issues relate to land ownership, mobilities within the region and the gradual dissemination of knowledge, skills and wealth. The book will provide both reference material and interesting reading for teachers, researchers and practitioners in interested in community based perspectives on sustainability. We have learnt from each other and hope that others will benefit from our efforts.".